Theoretical foundations of Treatment of Materials by Pulse Electron and Ion Beams: Text-book - Bleicher G. A. Galina A. (Учебники Томского политехнического университета)
The text-book contains the foundations of energy dissipation processes of pulse charged particles beams in the substance. Their knowledge is necessary for successful development and effective application of modern technologies of materials treatment by energy concentrated flows. The fundamental regularities of heat, thermo-mechanical and mass-transfer processes taking place in solids under the effect of submicrosecond ions and electrons beams are considered. The text-book is intended for the theoretical schooling of the students and undergraduates of International Education Institute at TPU who study according the programs "Plasma Physics", "High Voltage Engineering and Physics", "Substance Condensed State Physics", "Megaelectronics" and so on.